Food Purchase Location by Urbanization Level Among U.S. Population 2 Years and Older, NHANES 2013–2018 - Ansai, Nicholas (Curr Dev Nutr, 2021)
OBJECTIVES: To describe food purchase locations among U.S. persons aged 2 years and older by level of urbanization. METHODS: Data from 23,107 participants aged 2 and older from the National Health and Nutrition Examination Survey 2013–2018 were used to examine four food purchasing locations: fast food, grocery stores, convenience stores, and restaurants. The % of the U.S. population consuming food obtained from each location and mean ratios of % of total calories obtained on a given day were calculated. Estimates were presented by urbanization (large metropolitan statistical areas (MSAs), medium or small MSAs, and non-MSAs) overall and within age, sex, and income subgroups. All estimates were age-adjusted and tests for linear trends by urbanization were conducted using orthogonal polynomials with P < 0.05 significance level. RESULTS: The % of the U.S. population consuming fast food and the mean % of total calories from fast food on a given day increased with urbanization (30.2% in non-MSAs and 11.4% of calories, 36.5% in small/medium MSAs and 13.7% of calories, and 39.9% in large MSAs and 15.0% of calories). There were no trends by urbanization in the % consuming food from grocery stores or the % of calories from grocery stores. The % of the population consuming food from convenience stores and the % of total calories from convenience store food decreased with urbanization (28.9% in non-MSAs and 6.4% of calories, 26.6% in small/medium MSAs and 5.0% of calories, and 22.1% in large MSAs and 3.9% of calories). The % consuming food from restaurants and the % of total calories from restaurants increased with urbanization (14.1% in non-MSAs and 6.0% of calories, 18.3% in small/medium MSAs and 7.7% of calories, and 21.5% in large MSAs and 8.6% of calories). CONCLUSIONS: The % of the U.S. population consuming fast food and restaurant food on a given day increased with increasing urbanization level while the % of the population consuming convenience store food decreased. The mean % of total calories from each food purchase location followed the same trends by urbanization. More research may be needed to characterize the foods and nutritional quality of foods from these locations. FUNDING SOURCES: None.